2002
DOI: 10.1081/agb-120006486
|View full text |Cite
|
Sign up to set email alerts
|

CLASSIFICATION OF INVOLUTIONS OF SL(2, k)

Abstract: Abstract. In this paper we give a simple characterization of the isomorphy classes of involutions of SL(2, k) with k any field of characteristic not 2. We also classify the isomorphy classes of involutions for k algebraically closed, the real numbers, the ᒍ-adic numbers and finite fields. We determine in which cases the corresponding fixed point group H is k-anisotropic. In those cases the corresponding symmetric k-variety consists of semisimple elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…The primary motivation is to extend Helminck's [14] study of k-involutions and symmetric k-varieties to include fields of characterstic 2. This has been studied for groups of type G 2 and A n in [19,22] and over fields of characteristic not 2 in [6,3,2,4,16,17,18]. We also extend the results of Aschbacher and Seitz [1] who studied similar structures for finite fields of characteristic 2.…”
Section: Introductionsupporting
confidence: 62%
“…The primary motivation is to extend Helminck's [14] study of k-involutions and symmetric k-varieties to include fields of characterstic 2. This has been studied for groups of type G 2 and A n in [19,22] and over fields of characteristic not 2 in [6,3,2,4,16,17,18]. We also extend the results of Aschbacher and Seitz [1] who studied similar structures for finite fields of characteristic 2.…”
Section: Introductionsupporting
confidence: 62%
“…This project was inspired by the work of Wu in [9] and [6] where he determined involutions of SL(n, k) for fields of characteristic not 2, as well as for the group SO(2n + 1, k). This last was expanded on and improved by Benim and others in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Let G = SL(2, k). In [HW02] it was shown that any involution of G is isomorphic to one of the form σ a (x) = Int(A)(x) with A = 0 1 a 0 and a ∈ k * /(k * ) 2 . If H a is the fixed point group of σ a , then H a = x y ay x x 2 −ay 2 = 1 is k-anisotropic if and only if a = 1.…”
Section: 2mentioning
confidence: 99%